PENGARUH IMPLEMENTASI PERATURAN DAERAH PROVINSI SUMATERA UTARA NOMOR 3 TAHUN 2014 TERHADAP PENCEGAHAN KEKERASAN ANAK DI KECAMATAN MEDAN DENAI - Nomela Rismawati Br Sitorus; Artha Tobing; Jhonson Pasaribu (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the effect of the implementation of North Sumatra Provincial Regional Regulation Number 3 of 2014 on efforts to prevent violence against children in Medan Denai District. The type of research used in this study is a quantitative approach. The population in this study consists of people who reside in Medan Denai District with a sample of 100 respondents. The types of data used in this research are primary data and secondary data. Data collection techniques were carried out through the distribution of questionnaires to respondents. The data analysis methods used include instrument testing consisting of validity and reliability tests, descriptive statistical analysis, classical assumption tests consisting of normality tests, simple linear regression analysis, hypothesis testing through the t-test, and the coefficient of determination (R²).The results of the study indicate that the implementation of North Sumatra Provincial Regional Regulation Number 3 of 2014 has a positive and significant effect on the prevention of violence against children in Medan Denai District. This is indicated by the value of t count (6.189) > t table (1.660) and a significance value of 0.000 < 0.05. The coefficient of determination (R²) obtained is 0.281, which shows that the implementation of regional regulation variable is able to explain the influence on the prevention of violence against children by 28.1%, while the remaining 71.9% is influenced by other variables outside this study.